Optimizing the Role of the Prosecutor's Office in Recovering State Losses Due to Corruption Crimes Based on Prosecutor's Regulation Number 7 of 2020 concerning Guidelines for Asset Recovery - Ruth Irmawaty; Yandi (Journal of Law, Politic and Humanities, 2024)
The aim to be achieved in this research is to optimize the role of the prosecutor's office in recovering state losses resulting from criminal acts of corruption.  The method used in analyzing this problem is normative juridical where researchers use various secondary materials or library materials. The various steps taken in solving the problems in this research were by drawing on various legal principles, both written and unwritten. Researchers also carry out various interpretations of legislation so that this research can be analyzed thoroughly and in depth. The results of this research show that the objectives of asset recovery are varied. First, asset recovery aims to replenish state finances, thereby providing resources for government initiatives and programs aimed at improving people's welfare and fostering community well-being. Second, asset recovery aims to restore justice in the lives of individuals affected by corruption, ensuring that those who have been harmed receive compensation. Lastly, asset recovery seeks to deter parties or individuals from committing corruption in the future by signaling the severity of the consequences associated with such actions. Therefore, corruption needs to be dealt with, where one of the officers who can deal with this is the prosecutor's office. The Prosecutor's Office of the Republic of Indonesia, to confiscate assets for criminal acts of corruption, can work optimally if it has a basis for confiscating assets.